An ethics committee in the third sector: process and pitfalls - Ruby Whitelaw; Dan Johnson (Scottish Journal of Residential Child Care)
This article describes the lessons learned from introducing and establishing an ethics committee in a large third sector care provider. The article hopes to encourage other organisations to introduce similar committees and to help avoid potential problems and give advice on how to navigate others. It also hopes to give researchers and students insight into how a committee works and therefore perhaps how to apply in a way that maximises the chances of ethical research being accepted and completed.